Sistem Pendukung Keputusan Pemberian Bantuan Ekonomi Menggunakan Algoritma C4.5 - Agustiena Merdekawati; Luci Kanti Rahayu (Jurnal Serambi Engineering, 2021)
The problem that often appears in the distribution of economic assistance is miss-targeting assistance. This miss-targeted distribution is also faced by Baitul Maal Yayasan Al-Anshor Asmawiah, a foundation that receives and distributes economic aid. This obstacle is faced due to the many criteria attributes of potential recipients, confusing the foundation in selecting aid recipients and some parties are still cheating. Information provided by potential beneficiaries is often incomplete so there is a lack of data on the prospective beneficiary forms. The method for selecting economic aid is the C4.5 algorithm, which is an algorithm that forms a decision tree as a reference for selecting economic assistance. After obtaining the rules, the foundation implements the system in assisting. This system makes it easier for the public to fill out economic assistance forms and it is easy to immediately find out information whether they reserve the right to economic assistance or not and make it easier for administrators to get information divided to whom reserve the right to attain assistance.